Peningkatan Hasil Belajar Peserta Didik Melalui Penggunaan Model PBJL Pada Mata Pelajaran PAI Dan BP di Kelas X SMAN 2 Pangkalan Koto Baru - Hamadi, Candra (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in the Islamic Religious Education and Character (PAI and BP) subject on the topic of maintaining human dignity by avoiding free association and immoral acts through the implementation of the Project-Based Learning (PjBL) model. The research was conducted in Class X of SMAN 2, Pangkalan Koto Baru District, using a classroom action research method involving two cycles. Data were collected through tests, observations, and documentation and analyzed using quantitative and qualitative approaches. The results showed a significant improvement in students' learning outcomes, both in terms of understanding and engagement in learning. In Cycle I, students began to participate in group discussions and learning activities, while in Cycle II, they became more active, creative, and capable of producing educational projects such as moral campaign posters and videos. This study concludes that the PjBL model effectively improves student learning outcomes and provides a more meaningful and relevant learning experience for students in their daily lives.